Pinjaman Online Legal: Sebuah Tanggung Jawab Otoritas Jasa Keuangan - Putri, Devina Athalia; Dwiyatmi, Sri Harini (Widya Yuridika, 2024)
Technological developments are moving very quickly, so that almost all sectors have been impacted by technology itself, one of which is the financial sector which has given birth to an online-based financial service called Legal Online Loans (Pinjol Legal), which aims to make it easier for people to borrow money. However, since the emergence of Pinjol Legal, problems felt by the public have continued to emerge and to date the Financial Services Authority (OJK) as an independent institution responsible for protection, both for consumers and business actors, assisted by the Indonesian Funding Fintech Association (AFPI) has not issued clearly codified regulations regarding the focus on Pinjol Legal. Victims continue to increase and the policies provided have not fully responded to public concerns. Therefore, OJK's responsibility is still being questioned, so the author raises this issue by using a type of normative juridical research that uses a statutory approach and a case approach, with the addition of 2 (two) types of legal material sources. legal materials, namely primary legal materials in the form of legislation and secondary legal materials in the form of official documents, books and legal journals. This article will explain OJK's responsibilities, what OJK has done, the reality of legal lending in the field, and what regulations relate to legal lending. So the author provides suggestions for the OJK to make regulations regarding fixed interest rate limits, provide dispensation to consumers to extend loan payments on legal loans, and have a core supervisory team that helps the OJK and AFPI in supervising legal loans that have violated OJK's provisions and AFPI decides